Acupuncture-induced hemothorax with hypovolemic shock: a case report - Ghanad, Erfan; Reißfelder, Christoph; Yang, Cui (Journal of integrative and complementary medicine, 2023)
This report describes a very rare but life-threatening complication that occurred in a 43-year-old woman after an acupuncture (AC) for lumbago. The patient presented to the emergency department displaying symptoms indicative of shock. Physical examination revealed the absence of breath sounds on the right thoracic side, further investigations indicated the presence of a hemothorax. Emergency surgery was performed to evacuate the hemothorax and control bleeding from two intercostal veins. Although AC is often considered a gentle form of medicine, it is important to recognize that it can occasionally result in severe complications, especially when acupoints are used on the thorax.